Buffalo Milk Yield, Quality, and Marketing in Different Agro-Climatic Districts of Bangladesh (Journal of Buffalo Science, 2019)
The study was aimed at assessing the productive performance of dairy buffalo and milk marketing approaches in different agro-climatic districts of Bangladesh. Three (03) districts of Bangladesh viz. Bhola, Mymensingh, and Dinajpur were chosen from the coastal, river basin and semi-arid region, respectively. A triangulation method of survey was used to collect the data and the components of the triangle were buffalo farms, buffalo farmers and buffalo herdsmen. The investigation duration was twelve (12) months. The study revealed that the highest milk yield (5 L/h/d; p=0.010) was found in the river basin and semi-arid region. Lactation yield was also recorded double in the river basin and semi-arid districts compared to coastal districts (p=0.000). In the case of lactation length, the river basin buffaloes possessed 33 and 36% longer than coastal and semi-arid districts, respectively. All the chemical components were found significantly different (p≤0.050) but fat. Among different agro-climatic districts, about 92% of milk was traded in the coastal region after meeting the household's need but it was noted that the farmers from the semi-arid region kept more than 21% of milk for family consumption (p=0.000). The highest unit price (BDT 72/L) of milk was observed in the river basin district (p=0.011). In conclusion, the current situations of buffalo farming and milk marketing approaches in Bangladesh, varies considerably.